32/#1068 Trends in the incidence of ovarian germ cell cancers in us Asians and native Chinese. (4th December 2022) - Liao, Cheng-I; Aryasomayajula, Chinmayi; Johnson, Caitlin; Darcy, Kathleen; Tian, Chunqiao; Chan, Ava; Kapp, Daniel; Chan, John K
Abstract : Objectives: To identify trends in incidences of germ cell tumors and subtypes in large population registries in the US and Republic of China. Methods: Data was obtained from the United States Cancer Statistics (USCS) and the Taiwan Cancer Registry between 2001 and 2018. SEER*Stat and Joinpoint regression programs were used to calculate incidences and trends. Native Chinese were defined as individuals from Taiwan. The incidence was adjusted by WHO 2000 standard population. Results: Of 11, 941 patients with germ cell tumors, 651 (5.5%) were US Asians and 1249 (10.5%) were Native Chinese. Over the 17-year study period, the overall incidence of germ cell cancers in Native Chinese is nearly 2-fold higher compared to US Asians 0.66 vs. 0.36 per 100, 000. In Native Chinese, the incidence is increasing with an average annual percent change (AAPC) at 1.4% (p=0.006) whereas in US Asians there is no change (AAPC=-0.10%, p=0.89). To further evaluate the trends in Native Chinese, we found that the incidence (in 2018) of immature teratomas was nearly 3-fold higher compared to dysgerminoma and yolk-sac tumors (0.32 vs. 0.11 vs. 0.10). Moreover, immature teratomas are increasing at 3.46% per year (p<0.001) whereas the dysgerminoma and yolk-sac tumors have remained stable. An intersectional analysis showed Native Chinese at age 10–14 with immature teratoma had the highest annual increase (7.56%, p=0.016). Conclusions: Incidences of germ cell tumors have increased in Native Chinese but remained stable in US Asians. The higher incidence and increasing rates of the immature teratoma subtype warrants further studies on potential genetic and environmental factors.